Crystalline silica-induced proinflammatory eicosanoid storm in novel alveolar macrophage model quelled by docosahexaenoic acid supplementation - Favor, Olivia K.; Rajasinghe, Lichchavi D.; Wierenga, Kathryn A.; Maddipati, Krishna R.; Lee, Kin Sing Stephen; Olive, Andrew J.; Pestka, James J. (Frontiers in Immunology, 2023)
Introduction: Phagocytosis of inhaled crystalline silica (cSiO2) particles by resident alveolar macrophages (AMs) initiates generation of proinflammatory eicosanoids derived from the ω-6 polyunsaturated fatty acid (PUFA) arachidonic acid (ARA) that contribute to chronic inflammatory disease in the lung. While supplementation with the ω-3 PUFA docosahexaenoic acid (DHA) may influence injurious cSiO2-triggered oxylipin responses, in vitro investigation of this hypothesis in physiologically relevant AMs is challenging due to their short-lived nature and low recovery numbers from mouse lung. To overcome these challenges, we employed fetal liver-derived alveolar-like macrophages (FLAMs), a self-renewing surrogate that is phenotypically representative of primary lung AMs, to discern how DHA influences cSiO2-induced eicosanoids.Methods: We first compared how delivery of 25 µM DHA as ethanolic suspensions or as bovine serum albumin (BSA) complexes to C57BL/6 FLAMs impacts phospholipid fatty acid content. We subsequently treated FLAMs with 25 µM ethanolic DHA or ethanol vehicle (VEH) for 24 h, with or without LPS priming for 2 h, and with or without cSiO2 for 1.5 or 4 h and then measured oxylipin production by LC-MS lipidomics targeting for 156 oxylipins. Results were further related to concurrent proinflammatory cytokine production and cell death induction.Results: DHA delivery as ethanolic suspensions or BSA complexes were similarly effective at increasing ω-3 PUFA content of phospholipids while decreasing the ω-6 PUFA arachidonic acid (ARA) and the ω-9 monounsaturated fatty acid oleic acid. cSiO2 time-dependently elicited myriad ARA-derived eicosanoids consisting of prostaglandins, leukotrienes, thromboxanes, and hydroxyeicosatetraenoic acids in unprimed and LPS-primed FLAMs. This cSiO2-induced eicosanoid storm was dramatically suppressed in DHA-supplemented FLAMs which instead produced potentially pro-resolving DHA-derived docosanoids. cSiO2 elicited marked IL-1α, IL-1β, and TNF-α release after 1.5 and 4 h of cSiO2 exposure in LPS-primed FLAMs which was significantly inhibited by DHA. DHA did not affect cSiO2-triggered death induction of unprimed FLAMs but modestly enhanced it in LPSprimed FLAMs.Discussion: FLAMs are amenable to lipidome modulation by DHA which suppresses cSiO2-triggered production of ARA-derived eicosanoids and proinflammatory cytokines. FLAMs are an exciting potential in vitro alternative to primary AMs for investigating interventions against early toxicanttriggered inflammation in the lung.